2020
DOI: 10.1111/jfpp.15082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of high hydrostatic pressure treatment on Spanish and Portuguese traditional chorizos and evolution at different storage temperatures

Abstract: Half pieces of vacuum‐packaged traditional chorizos with different characteristics from Spain and Portugal were treated by high hydrostatic pressure (HHP) in order to increase their stability during storage. Microbiological, physical‐chemical, oxidative, and sensory changes were evaluated during the storage at 4°C and 20°C for 180 days. HHP was effective for the reduction of microorganisms’ counts. In both chorizos, instrumental color was modified after HHP. Lipid oxidation was not modified by HHP, although at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
10
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 55 publications
15
10
1
1
Order By: Relevance
“…In our study, the pH was over that usual range. The fat and protein content and the fatty acid profile were in line with results from previous studies [13].…”
Section: Initial Chorizo Characterizationsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, the pH was over that usual range. The fat and protein content and the fatty acid profile were in line with results from previous studies [13].…”
Section: Initial Chorizo Characterizationsupporting
confidence: 91%
“…However, most studies on Iberian chorizo have been performed on products with a w and pH within the usual ranges. The only study available on high a w and pH Iberian chorizo was not performed on sliced chorizo but on whole and half pieces, and showed that HPP increased the initial counts of mesophilic aerobic bacteria and lactic acid bacteria, challenging the feasibility of HPP to reduce the total microbial counts [13]. The increasing importance of sliced chorizo and the additional steps involved (casing removal, slicing and packaging) that favor quality loss and contamination with ubiquitous pathogens make it necessary to research the convenience of HPP to control the microbial counts in sliced chorizo with high a w and pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The initial pH at day 0 in DFS without starter culture added and without HPP (A-INP), was 6.0 ± 0.1, which is in agreement with results from previous studies with south European DFS (Juárez-Castelán et al, 2019;Martín et al, 2021;Rodríguez-González, Fonseca, Centeno, & Carballo, 2020). The pH drop was more pronounced initially in sausages with starter (p < 0.05), similar to what Latorre-Moratalla et al ( 2007) found.…”
Section: Evolution Of Physicochemical Parameterssupporting
confidence: 91%
“…These results partially match previous results, which reported lower counts for the mesophilic bacteria and molds and yeast using 20°C than at 4°C for 120day storage in Cebo loin (Cava et al, 2021). Although there is no previous information about the effect of the storage temperature on the LAB in loin, the results (Tables 3 and 4) are generally in line with those reported in chorizo, with lower counts after storage at 20°C than at 4°C (Carrapiso et al, 2023;Martin et al, 2021;Trejo et al, 2021). The lower counts at 20°C than at 4°C in those microorganisms also matches the results for the L. monocytogenes counts in Cebo loin (Cava et al, 2021) and other dry-cured Iberian products (Cava et al, 2020(Cava et al, , 2021.…”
Section: Effect Of Storage Temperaturesupporting
confidence: 90%